Risk of Progression of Subclinical to Overt Hypothyroidism: A Cohort Study - Kaur, Premjeet; Singh, Rakendra (Annals of Pathology and Laboratory Medicine, 2025)
Background: Subclinical hypothyroidism is defined by elevated serum thyroid stimulating hormone levels in the setting of normal levels of the thyroxine (T4) and triiodothyronine (T3). Iron acts as a cofactor in Thyroid peroxidase, which catalyses the initial two reactions of T3 and T4 biosynthesis. The chief clinical marker of iron deficiency is serum ferritin, which reflects the body iron stores. Whether hypoferritinemia affects the development of overt hypothyroidism from subclinical hypothyroidism is a question of concern. Methods: Aim: To determine the predictive significance of serum ferritin in subclinical hypothyroidism. Material and method: A cohort observational study was carried out at Adesh Institute of Medical Sciences and Research (AIMSR), Bathinda, India from June 2023 to December 2024 in Biochemistry department in collaboration with Medicine department, among 95 subjects of subclinical hypothyroidism attending the medicine outpatient department. Results: A total of 29 (30.53%) patients of subclinical hypothyroidism were converted to overt hypothyroidism by the end of 6 months. While in subjects with normal ferritin levels (>30µg/L) and low ferritin levels (15-30 µg/L) the conversion of subclinical hypothyroidism (TSH=7.09±1.33 µIU/mL) in normal ferritin subgroup, TSH=7.23±1.74 µIU/mL in low ferritin subgroup) to overt hypothyroidism (TSH=8.73±4.31 µIU/mL in normal ferritin subgroup, TSH=13.02±8.26 µIU/mL in low ferritin subgroup) was non-significant with p values p=0.51 and p=0.06) respectively. The conversion of subclinical hypothyroidism ( TSH=8.02±1.34 µIU/m) to overt hypothyroidism (TSH =13.86±8.49 µIU/mL) was significant (p=0.005) in subclinical hypothyroid patients with very low ferritin levels (<15 µg/L. Conclusion: Monitoring and correcting ferritin levels could be important in managing subclinical hypothyroidism to prevent progression.